Preoperative tumour size as a predictor of the presence of lymphovascular invasion in lung adenocarcinoma - Kemal Grbić; Bakir Mehić; Dalma Udovičić-Gagula; Amina Valjevac; Adem Ćemerlić; Ferid Krupić (Medicinski glasnik, 2020)
Aim: To examine whether preoperative tumour size may serve as a biomarker for the occurrence of lymphovascular invasion (LVI) in centrally and peripherally located lung adenocarcinoma. Method: The study included 261 patients surgically treated for diagnosed lung adenocarcinoma. A ROC curve was used to determine the biomarker potential of tumour size relative to the occurrence of LVI. Binary logistic regression was used to show changes of tumour size impact on the status of LVI. Result: Tumour prevalence according to localization had no statistical significance (p=0.464), while the presence of LVI in central, as well as peripheral positions, was statistically significantly different (p<0.001). The area under the curve of 0.978 highlights the fact that tumour size is an excellent marker of the presence of LVI in centrally located adenocarcinomas of the lung. A similar finding was confirmed in peripherally located lung adenocarcinomas with an area below the curve of 0.943. Binary logistical regression showed that in centrally localized adenocarcinomas of the lung, each additional centimetre of tumour growth represents an increase in the likelihood of LVI+ by 17.14 times. In peripherally located adenocarcinomas of the lung, this increase in likelihood of LVI for each centimetre of growth was 5.46 times. Conclusion: With a high degree of sensitivity and specificity, preoperative tumour size may serve as an important biomarker and positive predictor of the presence of LVI in lung adenocarcinoma of any location.
Keywords: binary logistical regression; CT scanning; histopathological examination; surgical resection; T-descriptor